The Effect of Job Satisfaction on Employee Retention - Hulu, Winer Berkat Jaya; Telaumbanua, Eliagus; Halawa, Odaligoziduhu; Mendofa, Yupiter (Golden Ratio of Data in Summary, 2025)
This study aims to determine whether job satisfaction influences employee retention at CV. Golden Mart and to measure the extent of this influence. The research problem addressed is whether job satisfaction significantly affects employee retention in this organization. A quantitative research approach was employed, involving statistical analysis to draw conclusions. The population of this study consists of all 30 employees of CV. Golden Mart, and the entire population was used as the sample. Data collection utilized both primary and secondary sources. The findings of this study indicate that job satisfaction has a positive effect on employee retention. This conclusion is supported by data processing results showing a significance value (Sig.) of less than 0.05. The reliability test demonstrated Cronbach's Alpha values of 0.886 for the job satisfaction variable and 0.842 for the employee retention variable, indicating that both variables are reliable as their Cronbach's Alpha values exceed 0.6. Furthermore, autocorrelation analysis using the runs test method yielded a value of 0.041, suggesting no autocorrelation in the data since the significant value exceeds 0.05. The coefficient of determination (R Square) was calculated at 0.787, indicating that 79% of employee retention can be explained by job satisfaction. The t-test results further confirmed that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected, affirming a significant influence of job satisfaction on employee retention at CV. Golden Mart in Gunungsitoli. The analysis also highlights specific indicators of job satisfaction and employee retention. For the job satisfaction variable, the strongest indicators include supervision, wages/salary, and coworker relationships, while weaker indicators are job characteristics and promotion opportunities. Regarding employee retention, the most prominent indicators are organizational components, rewards, and employee relations, whereas career opportunities and job design are the least significant. These findings provide valuable insights into the relationship between job satisfaction and employee retention at CV. Golden Mart.